Abundance and natural food resources of birds in Manusela National Park, Seram, Central Mollucas (Biodiversitas Journal of Biological Diversity, 2016)
The aim of this research was to know the abundance and natural food resources of birds in the Manusela National Park, Seram (Ceram), Central Moluccas. The observations were done by â€œline-transect methodsâ€, which in observe 70.50 hours totality. The results were found 51 species of birds in area of the national parks and 4 of all, namely red lory (Eos bornea), papuan hornbill (Rhyticeros plicatus), shining starling (Aplonis metallica), and grey-necked friarbird (Philemon subcorniculatus) were abundant. Fourty seven species of plants were known useful for 19 species of birds as the natural food resources, nesting-sites and roosting trees. Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: species diversity, abundance, natural food resources, national park, Manusela